TRANSFER PEMERINTAH PUSAT SEBAGAI WUJUD DESENTRALISI FISKAL DALAM PERTUMBUHAN EKONOMI DAERAH SEBAGAI BENTUK UPAYA MENGATASI KETIMPANGAN PENDAPATAN, EFEKTIF ATAU TIDAK? (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2022)
This study aims to determine the effectiveness of central government transfers to local governments in the current era of autonomy as a form of fiscal decentralization as a form of eliminating inequality in Indonesia. The writing method uses qualitative methods with comprehensive analysis and obtaining secondary data. Central Government and the use of public funds according to the priorities and aspirations of the community. Therefore, conditions like this, the role of private investment and regionally-owned companies are highly expected as the main drivers of regional economic growth and development. This means that fiscal decentralization in this autonomous era cannot be said to be fully effective